Orbits and masses in the multiple system LHS 1070 - Köhler, Rainer; Ratzka, Thorsten; Leinert, Christoph (Astronomy and astrophysics, 2012)
We present a study of the orbits of the triple system LHS 1070, with the aim to determine individual masses of its components.Methods. Sixteen new relative astrometric positions of the three components in the K band were obtained with NACO at the VLT, Omega CASS at the 3.5 m telescope on Calar Alto, and other high-spatial-resolution instruments. We combined them with data from the literature and fit orbit models to the dataset. We derived an improved fit for the orbit of LHS 1070 B and C around each other, and an estimate for the orbit of B and C around A.Results. The orbits are nearly coplanar, with a misalignment angle of less than 10°. The masses of the three components are MA = 0.13...0.16 M⊙, MB = 0.077 ± 0.005 M⊙, and MC = 0.071 ± 0.004 M⊙. Therefore, LHS 1070 C is certainly, and LHS 1070 B probably a brown dwarf. Comparison with theoretical isochrones shows that LHS 1070 A is either fainter or more massive than expected. One possible explanation would be that it is a binary. However, the close companion reported previously could not be confirmed.
Gesehen am 07.11.2018